STRATEGIC THINKING: (REVIEW ARTICLE) - Reyam Qasim Mohammed (Scholar Express Journals, 2025)
Strategic thinking is undoubtedly one of the most important managerial and intellectual skills that decisively play a key role in guiding individuals and organizations effectively toward long-term success in environments increasingly characterized by continuous change and complexity. Strategic thinking clearly goes beyond traditional planning; it primarily relies on a longterm vision, future forecasting, and linking goals with available resources and opportunities in a flexibly and creatively adaptive manner. This type of thinking generally involves a set of mental abilities, such as systematically conducted analysis, critically engaged thinking, and coherently integrating fragmented information, as well as the ability to accurately anticipate challenges and respond proactively. Various models and theories related to strategic thinking currently exist, yet most commonly agree on the importance of a clearly defined vision, flexibly executed implementation, and closely aligned internal and external environments. Due to the increasing significance of this concept in the fields of business, leadership, and policymaking, it has rightfully become a central topic in recent research and studies, especially amid contemporary challenges that urgently require deep and unconventionally structured thinking.
Keywords: Strategic thinking; Future vision; Policy making